2011
DOI: 10.1002/hep.24111
|View full text |Cite
|
Sign up to set email alerts
|

Loss of transforming growth factor β adaptor protein β-2 spectrin leads to delayed liver regeneration in mice

Abstract: Liver regeneration, following partial hepatectomy (PHx), occurs through precisely controlled and synchronized cell proliferation, in which quiescent hepatocytes undergo one to two rounds of replication, with restoration of liver mass and function. We previously demonstrated that loss of the Smad3/4 adaptor protein b-2 spectrin (b2SP) is associated with faster entry into S phase, and hepatocellular cancer formation. These observations led us to further pursue the role of b2SP in cell cycle progression in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…One molecular mechanism for how liver cells can escape from the cytostatic TGF-β response was described by the work of Mishra and coworkers [14,15,16,17,18,19,20,21,22,23,24]. Initially, they found that disruption of the adaptor protein ELF, a β-spectrin, leads to disruption of TGF-β/Smad signaling.…”
Section: Figmentioning
confidence: 99%
“…One molecular mechanism for how liver cells can escape from the cytostatic TGF-β response was described by the work of Mishra and coworkers [14,15,16,17,18,19,20,21,22,23,24]. Initially, they found that disruption of the adaptor protein ELF, a β-spectrin, leads to disruption of TGF-β/Smad signaling.…”
Section: Figmentioning
confidence: 99%
“…Currently, at least three stem cell populations are known to exist in both mouse27 and human adult liver28: 1) pericentral Axin2 + hepatocytes that can regenerate liver in normal homeostasis29; 2) periportal cells positive for Lgr530; 3) Prom1 + liver stem cells that are located within or adjacent to the Krt19 + bile duct epithelium 31. Human periportal cells also label for octamer 3/4 (Oct3/4), β2 spectrin (β2SP), and TBRII in both human and mouse liver regeneration 27, 28, 32.…”
Section: Liver Stem Cells and Tgf‐β: Evidence From Mouse Knockout LImentioning
confidence: 99%
“…Human periportal cells also label for octamer 3/4 (Oct3/4), β2 spectrin (β2SP), and TBRII in both human and mouse liver regeneration 27, 28, 32. Through previous studies in human liver donor and liver transplant specimens that represent human liver regeneration, as well as fulminant hepatic failure, putative liver progenitor/stem cell expansion has been observed during massive hepatic necrosis with fibrosis as well as submassive hepatic necrosis with hepatocytic lineage.…”
Section: Liver Stem Cells and Tgf‐β: Evidence From Mouse Knockout LImentioning
confidence: 99%
See 2 more Smart Citations